(untitled) (Scientific journal of the Fergana State University, 2025)
This article is described the effectiveness of advanced mnemonic techniques in language learning among senior-year students majoring in English teaching at Fergana State University. The results indicate that mnemonic techniques significantly enhanced memory and facilitated the recall of complex language concepts, particularly vocabulary and grammar rules.